Medications for sleep disturbance in children and adolescents with depression: a survey of Canadian child and adolescent psychiatrists - Addo Boafo; Stephanie Greenham; Marla Sullivan; Khalid Bazaid; Sinthuja Suntharalingam; Lana Silbernagel; Katherine Magner; Rébecca Robillard (BMC, 2020)
Abstract Background Primary care physicians and child and adolescent psychiatrists often treat sleep disturbances in children and adolescents with mood disorders using medications off-label, in the absence of clear evidence for efficacy, tolerability and short or long-term safety. This study is the first to report Canadian data about prescribing preferences and perceived effectiveness reported by child and adolescent psychiatrists regarding medications used to manage sleep disturbances in children and adolescents with depression. Methods Canadian child and adolescent psychiatrists were surveyed on their perception of effectiveness of a range of medications commonly prescribed for sleep disturbances, their ranked preferences for these medications, reasons for avoiding certain medications, and perceived side effects. Results Sixty-seven active child and adolescent psychiatrists completed the survey. Respondents reported noting significant sleep issues in 40% of all their patients. Melatonin and trazodone were identified as the first treatment of choice by 83% and 10% of respondents respectively, and trazodone was identified as the second treatment of choice by 56% of respondents for treating sleep disturbances in children and adolescents with depression. Melatonin (97%), trazodone (81%), and quetiapine (73%) were rated by a majority of respondents as effective. Doxepin, zaleplon, tricyclic antidepressants, zolpidem, or lorazepam were rarely prescribed due to lack of evidence and/or concerns about adverse effects, long-term safety, suitability for youth, suicidality, and dependence/tolerance. Conclusions Melatonin and certain off-label psychotropic drugs are perceived as being more effective and appropriate to address sleep disturbances in children and adolescents with depression. More empirical evidence on the efficacy, tolerability and indications for using these medications and newer group of sleep medications in this population is needed.